2010
DOI: 10.3354/dao02249
|View full text |Cite
|
Sign up to set email alerts
|

Amphibian pathogen Batrachochytrium dendrobatidis prevalence is correlated with season and not urbanization in central Virginia

Abstract: The global amphibian pathogen Batrachochytrium dendrobatidis (Bd) has been documented among many species throughout the United States, though cases of chytridiomycosis, the resulting disease, have occurred mostly on the west coast. We conducted a 2 yr survey of amphibians along an urban gradient in Virginia, USA, to test whether Bd prevalence among the amphibians sampled varied with urbanization and/or season. A total of 867 adult amphibians from 13 species and 49 tadpoles from 3 species were tested for Bd. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 34 publications
0
7
1
Order By: Relevance
“…For example, Gaertner et al [18] found an infection prevalence of 0.83 in cricket frogs ( Acris crepitans ) sampled in May from a site in central Texas. In Virginia, Pullen et al [19] found a peak prevalence of 0.45 across 13 semi-aquatic frog and salamander species. Sampling across seasons, Rothermel et al [17] found a prevalence of 0.18 in 12 species across four sites in Georgia, North Carolina, and South Carolina.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Gaertner et al [18] found an infection prevalence of 0.83 in cricket frogs ( Acris crepitans ) sampled in May from a site in central Texas. In Virginia, Pullen et al [19] found a peak prevalence of 0.45 across 13 semi-aquatic frog and salamander species. Sampling across seasons, Rothermel et al [17] found a prevalence of 0.18 in 12 species across four sites in Georgia, North Carolina, and South Carolina.…”
Section: Discussionmentioning
confidence: 99%
“…Infection was generally higher at the cooler high-elevation sites ( Fig. 2; Table S2), which may promote Bd growth and transmission compared to the low-elevation sites (Retallick 2002;Woodhams and Alford 2005;Brem and Lips 2008;Pullen et al 2010;Sapsford et al 2013). Variation in the infection rate may also be driven by differences among sites in the microhabitat use and movement patterns of frogs (Rowley and Alford 2007;.…”
Section: Infection and Recovery Ratesmentioning
confidence: 91%
“…In the wild, Bd prevalence is often higher in cooler seasons and lower in warmer ones (Woodhams and Alford 2005;Brem and Lips 2008;Voordouw et al 2010;Whitfield et al 2012;Sapsford et al 2013). Bd is more prevalent at higher elevations, presumably because temperatures are cooler (Woodhams and Alford 2005;Brem and Lips 2008;Pullen et al 2010;Sapsford et al 2013). Temperature may influence susceptibility to infection and disease-induced mortality.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 97%
“…Differences in an individual bacterial isolate's interactions with the environment and other microbes are also known to alter bacterial metabolite production (Daskin et al, 2014;Wolz et al, 2017;Medina et al, 2017a;Bird et al, 2018). Thus, another consideration is whether Bd is present and when is it most active, as changes in microbial community composition have been linked with the onset of Bd infection (Pullen et al, 2010;Longo et al, 2015;Clare et al, 2016;Varela et al, 2018). Specifically, Bd is more prevalent during seasons of moderate temperatures (between 17 and 25°C) and high precipitation.…”
Section: Spatial and Temporal Variation Within Genera And Speciesmentioning
confidence: 99%